Analisis Keamanan Atas Serangan Heartbleed pada Android yang Digunakan untuk Akses Lokal - Arifin, Arifin, Bana Handaga, S.T.,M.T.,P.h.D (2015)
There are kinds of vulnerabities in OpenSSL extentions, one of them is heartbleed. Heartbleed exploit security system by encrypt inputed text such as username and password. Input text attacked by heartbleed script which runing with command prompt or terminal in operating system. Therefore, hackers or attackers can record and exploit the informations. This Research did by 3 steps, first step by setup and configuration server sysem and client system. Second step by tested heartbleed vulnerability and third step by tested heartbleed using Heartbleed Detector and Heartbleed Scanner.The result said that problems not come from operating system but come from OpenSSL vulnerabilitiess.The problems from system could be overcame by upgrade to the last version OpenSSL 1.0.1i